Matrimonial property and legality of claiming it between fiqh and the laws of Malaysia, Morocco and Tunisia - Bosheya, Mohamed Shafei Moftah (Linguistics and Culture Review, 2021)
One of the most important goals of the marital relationship is the affection and compassion that drive spouses to cooperate together in earning their livelihood. When the marital relationship breaks down, each of the spouses would claim his/her share of the matrimonial property; such claim is different from the stipulated legal dues such as the inheritance and the alimony. The question is, what is the definition of the matrimonial property? Does this concept exist in the old Islamic jurisprudence? Is it legal to claim this money by one of the spouses or their heirs? And to what extent is the interest achieved or hardship avoided if the claimant is given his/her share? What is the position of the Malaysian Judiciary and its legal text on that issue? What is the stand of the official fatwa departments on this issue? What are the types of legal evidence cited by the different fatwas related to the matrimonial property? Moreover, are there countries other than Malaysia that have adopted this system?